Μ-XRF Studies on the Colour Brilliance in Ancient Wool Carpets. (10th January 2017) - Meyer, Markus; Borca, Camelia N.; Huthwelker, Thomas; Bieber, Manfred; Meßlinger, Karl; Fink, Rainer H.; Späth, Andreas
Abstract : Many handmade ancient and recent oriental wool carpets show outstanding brilliance and persistence of colour that is not achieved by common industrial dyeing procedures. Anthropologists have suggested the influence of wool fermentation prior to dyeing as key technique to achieve the high dyeing quality. By means of μ -XRF elemental mapping of mordant metals we corroborate this view and show a deep and homogenous penetration of colourants into fermented wool fibres. Furthermore we are able to apply this technique and prove that the fermentation process for ancient specimens cannot be investigated by standard methods due to the lack of intact cuticle layers. This finding suggests a broad range of further investigations that will contribute to a deeper understanding of the development of traditional dyeing techniques. Spectroscopic studies add information on the oxidation states of the metal ions within the respective mordant-dye-complexes and suggest a partial charge transfer as basis for a significant colour change when Fe mordants are used.